auto-update(nvim): 2025-01-10 12:44:05
Some checks failed
Deploy Quartz site to GitHub Pages using Nix / build (push) Has been cancelled
Deploy Quartz site to GitHub Pages using Nix / deploy (push) Has been cancelled

This commit is contained in:
Youwen Wu 2025-01-10 12:44:05 -08:00
parent bbd872861c
commit 66554ba4e0
Signed by: youwen5
GPG key ID: 865658ED1FE61EC3
2 changed files with 90 additions and 0 deletions

View file

@ -67,6 +67,15 @@ Attendance to discussion sections is mandatory.
- $y' = y^2$
]
#definition[
In general, a differential equation is called linear if and only if it can be
written in the form
$
a_n (t) (dif^n y) / (dif t^n) + a_(n-1) (t) (d^(n-1) y) / (d t^(n-1)) + dots + a_1 (t) (dif y) / (dif t) + a_0 (t) y = g(t)
$
where $a_k (t)$ and $g(t)$ are single variable functions of $t$.
]
#definition[
*Equilibrium solutions* for the ODE
$ y' = F(x,y) $
@ -87,3 +96,71 @@ Attendance to discussion sections is mandatory.
What are the equilibria of the equation
$ y' = y(y - x) $
]
== General solution of a first order linear ODE
We start with the differential equation in standard form
$ (dif y) / (dif t) + p(t) y = g(t) $
where $p(t)$ and $g(t)$ are continuous single variable functions of $t$.
Then let us assume the existence of an *integrating factor* $mu(t)$, such that
$ mu(t) p(t) = mu'(t) $
and then multiplying each term by $mu(t)$ to obtain
$ mu(t) (dif y) / (dif t) + mu(t) p(t) y = mu(t) g(t) $
Then
$ mu(t) (dif y) / (dif t) + mu'(t) y = mu(t) g(t) $
Then recognize that the left side of the equation is the product rule to obtain
$
(mu(t) y(t))' &= mu(t) g(t) \
integral (mu(t) y(t))' dif t &= integral mu(t) g(t) dif t \
mu(t) y(t) + C &= integral mu(t) g(t) dif t \
y(t) &= (integral mu(t) g(t) dif t + C) / (mu(t))
$
Now we have a general solution but we need to determine $mu(t)$.
$
mu(t) p(t) &= mu'(t) \
(mu'(t)) / (mu(t)) &= p(t) \
(ln mu(t))' &= p(t)
$
So now
$
integral mu(t) + k &= integral p(t) dif t \
ln mu(t) &= integral p(t) dif t + k \
mu(t) = e^(integral p(t) dif t + k) &= k e^(integral p(t) dif t)
$
Now substitute
$
y(t) &= (integral k e^(integral p(t) dif t) g(t) dif t + C) / (k e^(integral p(t))) \
&= (k integral e^(integral p(t) dif t) g(t) dif t + C) / (k e^(integral p(t)))
$
Now do some cursed constant manipulation to obtain a final solution with only one arbitrary constant
$
y(t) = (integral e^(integral p(t) dif t) g(t) dif t + C) / (e^(integral p(t)))
$
#remark[
The most useful result to us is
$
y(t) &= (integral mu(t) g(t) dif t + C) / (mu(t)) \
mu(t) &= e^(integral p(t) dif t)
$
We can easily obtain a solution form for any first order linear ODE simply by
identifying $p(t)$ and $g(t)$.
]

View file

@ -59,3 +59,16 @@ point or vector.
How far is the point $x_1, x_2, x_3$ from the origin? \
Answer: $x_1^2 + x_2^2 + x_3^2$
]
#definition[
For vectors $u$ and $v$, where
$ v = vec(v_1, v_2, dots.v, n), u = vec(u_1, u_2, dots.v, n) $
The dot product is defined as
$ sum_(i=1)^n v_i dot u_i $
]
#proposition[
The dot product of two vectors is the product of their magnitudes and the cosine of the angle between.
$ arrow(v) dot arrow(w) = ||arrow(v)|| dot ||arrow(w)|| cos theta $
]